A crusader’s tale from a journey through Byzantium: the letters of count Stephen of Blois to his wife Adela - Swinarski, Paweł (Balcanica Posnaniensia. Acta et studia, 2025)
The article presents in Polish and Latin languages two famous letters that Stephen-Henry, count of Chartres and Blois, sent to his wife Adela of Normandy during the First Crusade (1096–1099). The former of these, written c. 24 June 1097, recounts the reception of Stephen in Constantinople by emperor Alexius I Comnenus and the siege of Nicaea, while the latter, written on 29 March 1098, tells about the crusaders’ journey through Anatolia and the following siege of Antioch. Both sources have long been of great interest to historians due to their peculiar character and some original information on the events of the crusade. The letters’ text is accompanied by a commentary and an introduction, in which their research has been summarised. It is the first full scientific translation of these sources into Polish.